Effect of latanoprost on thyroid orbitopathy. (2nd November 2017) - Ha, Jerome; Zunz, Eran; Sagili, Suresh
ABSTRACT: Background : Prostaglandin F2α analogues are known to reduce human orbital fibroblasts proliferation and adipogenesis and may be used as a potential therapy for treatment of thyroid orbitopathy. The aim of this study was to identify any beneficial effect of latanoprost on thyroid orbitopathy, in the form of reduction in proptosis, secondary to prostaglandin associated periorbitopathy. Methods : A retrospective case review of 11 patients (22 eyes) with thyroid eye disease who were using latanoprost for management of ocular hypertension. Patients receiving systemic immunosuppressants were excluded. Orbital imaging was analysed where available. A change in proptosis was analysed based on Hertel exophthalmometry. Results : Three patients (27%) had ≥ 2 mm reduction in proptosis and they all had fat predominant thyroid orbitopathy, as evident on orbital imaging. Proptosis remained unchanged or improved by less than 2mm in the rest of the patients (73%). Overall, mean pre treatment exophthalmometry was 22.4 mm (range 15–30 mm) and mean post treatment exophthalmometry was 20.6 mm (range 15–29 mm). Conclusion : Latanoprost was well tolerated in patients with thyroid orbitopathy. Objective reduction in proptosis of 2mm or more was noted in 3 patients (27%) and none of the patients had an increase in proptosis. The improvement in proptosis may be more pronounced in patients with fat predominant orbits.